Analysis of indications of induction of labor and feto-maternal outcome in a tertiary care hospital - Sharma, Shuchi; Sharma, Reena; Gautam, Ankush (International Journal of Research in Medical Sciences, 2023)
Background: Induction of labor (IOL) is an intervention that artificially initiates uterine contractions leading to progressive dilatation and effacement of cervix and expulsion of fetus prior to spontaneous onset of labor. Aim of study was to study the indications of induction of labor and the feto-maternal outcome. Methods: Women who underwent IOL beyond 28 weeks gestation with single cephalic presentation were included in the study over a period of one year. Results: A total of 3887 women delivered in the hospital during the study period. 1107 (28.47%) pregnant women underwent induction of labor. Most common indication of induction of labor was post-date pregnancy 682 (61.60%). About 64.52% had vaginal delivery, 30.71% had caesarean section and 4.6% had instrumental delivery, 1.80% PPH, 0.45% puerperal sepsis and 2.16% wound sepsis. 97% neonates with APGAR score more than 7and 1.08% neonates were admitted to NICU. There were 0.27% fresh still births and 0.45% birth asphyxia. Conclusions: Careful analysis of indication of induction of labor, selection of the patients, proper monitoring at the time of induction and strict partographic management of labor results in a healthy baby and mother.